Analisis Data dalam Peningkatan Kualitas Pembelajaran pada SDN 1204 Padang Hasior - Intan Maimunah; Fitri Amelia Sari Lubis (Politeknik Ganesha Medan, 2025)
The improvement of learning quality in elementary schools requires a systematic approach based on data analysis. This research aims to analyze how data-driven strategies can enhance the quality of learning at SDN 1204 Padang Hasior. The study applies a descriptive quantitative method, using questionnaires and learning achievement data from students in grades IV–VI. Data were analyzed using simple linear regression to identify the relationship between teacher performance, learning environment, and student learning outcomes. The findings indicate that the use of data analysis significantly improves decision-making in teaching strategies, resulting in an increase in students’ academic performance by 18% compared to the previous semester. The research also reveals that teacher interventions based on data evaluation create a more engaging and effective learning environment. The conclusion suggests that integrating data analysis into school management and teaching practices can optimize the learning process. Further research is recommended to explore data-driven decision-making across different school contexts.